EMDR beyond PTSD: A Systematic Literature Review - Valiente-Gómez, Alicia; Moreno-Alcázar, Ana; Treen, Devi; Cedrón, Carlos; Colom, Francesc; Pérez, Víctor; Amann, Benedikt L. (Frontiers in Psychology, 2017)
Background: Eye Movement Desensitization and Reprocessing (EMDR) is a psychotherapeutic approach that has demonstrated efficacy in the treatment of Post-traumatic Stress Disorder (PTSD) through several randomized controlled trials (RCT). Solid evidence shows that traumatic events can contribute to the onset of severe mental disorders and can worsen their prognosis. The aim of this systematic review is to summarize the most important findings from RCT conducted in the treatment of comorbid traumatic events in psychosis, bipolar disorder, unipolar depression, anxiety disorders, substance use disorders, and chronic back pain. Methods: Using PubMed, ScienceDirect, and Scopus, we conducted a systematic literature search of RCT studies published up to December 2016 that used EMDR therapy in the mentioned psychiatric conditions. Results: RCT are still scarce in these comorbid conditions but the available evidence suggests that EMDR therapy improves trauma-associated symptoms and has a minor effect on the primary disorders by reaching partial symptomatic improvement. Conclusions: EMDR therapy could be a useful psychotherapy to treat trauma-associated symptoms in patients with comorbid psychiatric disorders. Preliminary evidence also suggests that EMDR therapy might be useful to improve psychotic or affective symptoms and could be an add-on treatment in chronic pain conditions.